FEASIBILITY ANALYSIS OF STATE-OWNED EXPERIMENTAL POND FARMS - Peterson, Richard E; Seo, K K (Indian Journal of Fisheries, 2011)
Creating a frustrating situation of inherent conflict between the long-rangeobjectives of scientists and the short-term needs of commercial growers, the currentsystem in Hawaii of obtaining data from the prawn farmers' ponds and using theponds to test management techniques and devices as a return for the subsidy providedin the form of free technical assistance and juveniles for stocking under athree-year period of assistance appears to cause a major bottleneck in industryprogress. The authors, taking this into consideration, propose state-owned experimentalfarm stations for an alternative and provide detailed methods for evaluatingtheir worthwhileness from both the scientists' and the growers' points of view.